The Relationship between Madrasah Principal Leadership and Teacher Performance at Madrasah Tsanawiyah - Badrun Badrun (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teacher performance will be optimal if the leadership of the madrasah principal is also optimal. This study aims to determine the relationship between the leadership of the madrasah principal and teacher performance at MTSN 1 Mataram City. The population of this study was all teachers of MTSN 1 Koata Mataram as many as 62 people. The research sample was taken using a stratified proportional random sampling technique so that the research sample was obtained by as many as 16 people. The principal leadership indicators used in this study were innovators, motivators, and supervisors; while the teacher performance indicators used in this study were learning planning and learning implementation. The data collection instrument used a questionnaire in the form of a google form. Data analysis to determine the relationship of principals' leadership with teacher performance using Pearson Correlation with the help of SPSS software. The results showed that there was a significant relationship between the leadership of the madrasah principal and teacher performance at MTSN 1 Mataram City. The relationship between the principal's leadership and teacher performance is included in a strong relationship.